2006
DOI: 10.1002/cncr.22267
|View full text |Cite
|
Sign up to set email alerts
|

Random control clinical trial on the effects of aerobic exercise training on erythrocyte levels during radiation treatment for breast cancer

Abstract: BACKGROUND.Erythrocyte changes from aerobic exercise training were examined during radiation treatment of breast cancer.METHODS.Twenty sedentary females with breast carcinoma who were ages 35 to 65 years were randomized to aerobic exercise (AE) of walking for 20 to 45 minutes, 3 to 5 times per week, at 50% to 70% of measured maximum heart rates or to placebo stretching (PS) activities 3 to 5 days per week during 7 weeks of radiation treatment. Measures were obtained 1 week before and after the radiation regime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 14 publications
4
60
0
Order By: Relevance
“…The results of this study agreed with that of Drouin et al, (2006) [10] who found that 7 weeks of moderate intensity aerobic exercise training (walking for 20-45 min, 3-5 times per week, at 50-70% of measured maximum heart rate) increase HCT, Hb, RBC and VO2 peak.…”
Section: Discussionsupporting
confidence: 91%
“…The results of this study agreed with that of Drouin et al, (2006) [10] who found that 7 weeks of moderate intensity aerobic exercise training (walking for 20-45 min, 3-5 times per week, at 50-70% of measured maximum heart rate) increase HCT, Hb, RBC and VO2 peak.…”
Section: Discussionsupporting
confidence: 91%
“…Evidence supports the benefit of exercise in managing fatigue during and after treatment for patients with breast cancer and other solid tumors (Courneya & Friedenreich, 1999;Galvao & Newton, 2005 (Drouin et al, 2006) suggest that exercise increases hemoglobin levels. Women receiving radiation treatment for breast cancer (N = 20) were randomly assigned to aerobic exercise or to placebo stretching during the seven-week treatment period.…”
Section: Design-randomized Clinical Trialmentioning
confidence: 98%
“…Although limited by small sample size, results from a recent randomized controlled trial (Drouin et al, 2006) suggest that exercise increases hemoglobin levels. Women receiving radiation treatment for breast cancer (N = 20) were randomly assigned to aerobic exercise or to placebo stretching during the seven-week treatment period.…”
Section: Key Pointsmentioning
confidence: 99%
“…ESAs increase Hb but they do not induce central (i.e., cardiac output) or peripheral (i.e., Hb extraction and use) adaptations [16,17]. Exercise training can improve these parameters with no expected change in Hb levels.…”
Section: Introductionmentioning
confidence: 99%